Mewujudkan merdeka belajar matematika: Kolaborasi deep learning dan trilogi pendidikan Ki Hadjar Dewantara - Hartanti Hartanti; Alifiani Alifiani; Anies Fuady (IKIP Siliwangi, 2026)
Mathematics learning in Indonesia still faces challenges in creating a meaningful, humanistic, and student-centered learning process, in accordance with the principles of Freedom to Learn. Although Deep Learning can improve conceptual understanding and critical thinking, and the Ki Hadjar Dewantara Education Trilogy strengthens the role of teachers as role models and facilitators, the integration of these two approaches has rarely been systematically studied. This study aims to analyze the collaboration of these two approaches through a Systematic Literature Review (SLR) based on the PRISMA guidelines (2022–2026), including the stages of identification, selection, feasibility, and synthesis of articles, with 9 relevant articles from 233 literature. The results of the study indicate that Deep Learning improves conceptual understanding, critical thinking, motivation, and student independence, while the Education Trilogy strengthens the role of teachers, thus forming a humanistic Freedom to Learn Mathematics.